Effective rehabilitation and closure planning: lessons from Base Titanium mine, Kwale, Kenya - Okello, N.; Vickers, D. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Mining in Kenya is in its infancy and Base Titanium mine, by far the largest mine and a subsidiary of Base Resources, has set global standards for mining sustainably. With over 10 years in operation and approaching completion of mining at the end of 2024, Base Titanium mine has received national and international recognition and awards for its mine rehabilitation and sustainability achievements. The Kwale mine is situated close to forests and remnant forest patches that constitute the Coastal Forests of Eastern Africa Biodiversity Hotspot, which support high biodiversity and numerous endemic plant species. The mine’s indigenous tree nursery represents one of the largest in East and Central Africa, in which several rare species considered of conservation significance have been successfully propagated for the first time. Among them are more than 90 that appear on the International Union for Nature Conservation Red List of Threatened Species as Critically Endangered, endangered or vulnerable. Two critically endangered trees (Euphorbia tanaensis and Gigasiphon macrosiphon) have been propagated and are listed among the world’s 100 most threatened plant, fungi and animal species. In this paper, we showcase the sustainability practices of Base Titanium Limited (BTL) that make it stand out as a leading example in the mining industry. Eight key areas are discussed: land capability and research-based post-mine use purpose-engineered landform design created wetlands co-disposal of sand and slime tailings for rehabilitation community-based seed, indigenous tree sourcing and propagation for restoration tails management, research and development stakeholder and community engagement employee closure transition preparation.